SEROEPIDEMIOLOGY OF TOXOPLASMA, RUBELLA, CYTOMEGALOVIRUS AND HERPES SIMPLEX VIRUS -2 IN WOMEN WITH BAD OBSTETRIC HISTORY. PART II. CYTOMEGALOVIRUS AND HERPES SIMPLEX VIRUS INFECTIONS - Abdulghani Mohamed Alsamarai; Zainab Khalil Mohamed Aljumaili (Our Dermatology Online, 2013)
Bad obstetric history (BOH) is reported worldwide and is associated with social and psychological impacts. Cytomegalovirus and herpes simplex virus play an important role in the induction of adverse outcomes of pregnancy. Highest CMV IgG prevalence rate was reported for India (91.05%), while the lowest rate was reported for Iran (14.28%). Unfortunately, six studies in Iraq reported a high prevalence of CMV IgM in non-married, pregnant and women with BOH. The range of recent CMV infection in pregnant women with BOH was from 1.4% in Jordan to 60.2% in Iraq. In women with BOH, the highest HSV 2 prevalence (16.8%) was noted in India, while the lowest rate (1.69%) was reported in India also. In Arab countries, among women with BOH, HSV 2 IgG and IgM seroprevalence higher rates were reported for Iraq. This literature review highlights the high bacterial and viral maternal infection rate in the developing world. Urgent, concerted action is required to reduce the burden of these infections. In addition to raising awareness about the severity of the problem of maternal infections in the developing world, data from this review will be beneficial in guiding public health policy, research interests and donor funding towards achieving improvement in health care delivery.